EFFECT OF AUTOMOBILE RELATED LEAD POLLUTION ON SPATIO-TEMPORAL DISTRIBUTION OF BIOCHEMICAL ATTRIBUTES ALONG ROADSIDE VEGETATION - AHMAD, I; HUSSAIN, T; LIAQUAT, M; ANJUM, S; SARWAR, M; AHMAD, S; ALI, Q; NASEEM, W; RIZVI, SA (Biological and Clinical Sciences Research Journal, 2023)
This research was carried out for the phyto-monitoring of pollution to check the effect of Pb2+ pollution on the spatio-temporal distribution of biochemical attributes resulting along Motorway M-2 and G.T. road Kharian to Taxila. The result showed that maximum decrease of total soluble sugars in Nerium oleander (0.023 mg/g F.wt) along M-2 and Calotropis procera (0.042 mg/g F.wt) along N-5, total free amino acid in Datura alba (0.501 mg/g F.wt) and Cenchrus ciliaris (0.62 mg/g F.wt) and total soluble proteins in Cenchrus ciliaris (3.91 mg/g F.wt) and Ricinus communis (0.73 mg/g F.wt) due to high concentration of Pb2+ (2.05-1.33 mg/kg dry wt.) along roadside. Findings may have their application as bio-indicators to perceive the occurrence of atmospheric pollutants on plants for identification and prediction of environmental hazards.